Sexual dichromatism and color diversity in the spiny lava lizard Tropidurus spinulosus using lizard visual modelling - Rossi, N. (2019)
Colors are important vehicles for social signals in many taxa. In Squamata, previous studies have linked color characteristics and chromatic diversity to sexual selection and, particularly, species showing male-biased body size dimorphism also showed male-biased dichromatism and color diversity. Sexual dichromatism may occur in body regions used for conspecific communication and it may be expressed at wavelengths, such as ultraviolet, easily perceivable by conspecifics. We tested this prediction in a social lizard model, Tropidurus spinulosus, using spectrophotometry and visual modelling which enable colors to be interpreted as the individuals of the same taxon see them. Our results indicate that sexual dichromatism occurs in the ventral regions and the flanks, which are the body regions involved in sexual displays. Males show greater color diversity, having larger color volumes and more contrasting colors. These findings reinforce the idea that sexual selection towards males is coupled with the evolution of male-biased, diverse, coloration which could act as a signal in social reproductive contexts.